2020
DOI: 10.1186/s12942-020-00220-6
|View full text |Cite
|
Sign up to set email alerts
|

Improving geographical accessibility modeling for operational use by local health actors

Abstract: Background: Geographical accessibility to health facilities remains one of the main barriers to access care in rural areas of the developing world. Although methods and tools exist to model geographic accessibility, the lack of basic geographic information prevents their widespread use at the local level for targeted program implementation. The aim of this study was to develop very precise, context-specific estimates of geographic accessibility to care in a rural district of Madagascar to help with the design … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 54 publications
0
50
0
2
Order By: Relevance
“…The population of children under five years old was estimated Finally, we used a geographic information system containing data on locations of all health centers, more than 20,000 km of footpaths, over 100,000 buildings, and nearly 5,000 residential areas in the district. This was obtained following a participatory complete mapping of Ifanadiana in 2018-2019, from very high resolution satellite images available through OpenStreetMap [35]. This data was queried on QGIS via the QuickOSM plugin and was used to estimate shortest path distances between health centers and each Fokontany.…”
Section: Data Collectionmentioning
confidence: 99%
“…The population of children under five years old was estimated Finally, we used a geographic information system containing data on locations of all health centers, more than 20,000 km of footpaths, over 100,000 buildings, and nearly 5,000 residential areas in the district. This was obtained following a participatory complete mapping of Ifanadiana in 2018-2019, from very high resolution satellite images available through OpenStreetMap [35]. This data was queried on QGIS via the QuickOSM plugin and was used to estimate shortest path distances between health centers and each Fokontany.…”
Section: Data Collectionmentioning
confidence: 99%
“…Rates increased to 60% to 85% across the idHSS catchment in 2016 and 2018, except for a remote area in one of the intervention communes (centre-right of the map), where populations have to travel over 4 hours by foot each way to reach the nearest health facility. 46 In the majority of the control catchment area, healthcare seeking BMJ Global Health behaviours for childhood illnesses remained consistently below 50% during the study period (figure 2). The idHSS intervention implemented by the MoPH-PIVOT partnership was associated with reductions in economic and geographical inequalities for most indicators assessed (figure 3, online supplemental tables S5 and S6).…”
Section: Changes In Geographical and Economic Inequalities In Mnch Comentioning
confidence: 97%
“…40 To estimate geographical inequalities, the Open Source Routing Machine (OSRM) engine was used to accurately estimate the shortest path distance between the villages in each cluster and the nearest health centre. For this, we had previously mapped the entire district of Ifanadiana on OpenStreetMap, resulting in over 23 000 km of footpaths and 5000 residential areas mapped (see 46 for details). For each indicator, we estimated wealth-specific and geographic-specific averages (bottom two quantiles vs top three quantiles) as well as composite indicators of inequality, such as relative concentration index and slope index of inequality.…”
mentioning
confidence: 99%
“…Although PIVOT initially focused its efforts on supporting the MOPH's facility-based care (via the CHRD, CSBs, and the referral network), evaluations of health-care access in Ifanadiana showed that while coverage of most essential health services rapidly improved over time, major geographic barriers to care left remote communities with persistent unmet primary care needs. 12,18 It was clear that PIVOT's financial and technical support needed to shift to include community-based care delivery via community health sites. Yet, the geography in Ifanadiana is such that many communities have poor geographic access to community health sites.…”
Section: Example 1-flexibility and Extending Reachmentioning
confidence: 99%
“…Yet, the geography in Ifanadiana is such that many communities have poor geographic access to community health sites. 18 To respond to this persistent challenge, and at the request of the MoPH, an innovative pilot to more actively meet the primary care needs of clients in their homes and communities was designed. The commune of Ranomafana has piloted a two-pronged approach to service delivery: one CHW is available at the community health site, while other CHWs travel a circuit of households throughout the fokontany to proactively identify sick children and provide basic care following a roster.…”
Section: Example 1-flexibility and Extending Reachmentioning
confidence: 99%